Technology-enabled activation of skin cancer screening for hematopoietic cell transplantation survivors and their primary care providers (TEACH) - Saro H. Armenian; Lanie Lindenfeld; Aleksi Iukuridze; Meagan Echevarria; Samantha Bebel; Catherine Coleman; Ryotaro Nakamura; Farah Abdullah; Badri Modi; Kevin C. Oeffinger; Karen M. Emmons; Ashfaq A. Marghoob; et al. (BMC Cancer, 2020)
Abstract Background Hematopoietic cell transplantation (HCT) is a curative option for a growing number of patients with hematologic diseases and malignancies. However, HCT-related factors, such as total body irradiation used for conditioning, graft-versus-host disease, and prolonged exposure to immunosuppressive therapy, result in very high risk for melanoma and non-melanoma skin cancer (NMSC). In fact, skin cancer is the most common subsequent neoplasm in HCT survivors, tending to develop at a time when survivors’ follow-up care has largely transitioned to the primary care setting. The goal of this study is to increase skin cancer screening rates among HCT survivors through patient-directed activation alone or in combination with physician-directed activation. The proposed intervention will identify facilitators of and barriers to risk-based screening in this population and help reduce the burden of cancer-related morbidity after HCT. Methods/design 720 HCT survivors will be enrolled in this 12-month randomized controlled trial. This study uses a comparative effectiveness design comparing (1) patient activation and education (PAE, N = 360) including text messaging and print materials to encourage and motivate skin examinations; (2) PAE plus primary care physician activation (PAE + Phys, N = 360) adding print materials for the physician on the HCT survivors’ increased risk of skin cancer and importance of conducting a full-body skin exam. Patients on the PAE + Phys arm will be further randomized 1:1 to the teledermoscopy (PAE + Phys+TD) adding physician receipt of a portable dermatoscope to upload images of suspect lesions for review by the study dermatologist and an online course with descriptions of dermoscopic images for skin cancers. Discussion When completed, this study will provide much-needed information regarding strategies to improve skin cancer detection in other high-risk (e.g. radiation-exposed) cancer survivor populations, and to facilitate screening and management of other late effects (e.g. cardiovascular, endocrine) in HCT survivors. Trial registration ClinicalTrials.gov, NCT04358276 . Registered 24 April 2020.